2014
DOI: 10.1308/003588414x13814021679311
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology and current management of prepubertal epididymitis

Abstract: INTRODUCTION The aim of this study was to review the published evidence on the pathogenesis and management of acute epididymitis (AE) in prepubertal boys after the authors encountered an unexpectedly large number of such cases in their institution. METHODS Using MEDLINE ® , a literature search was performed for articles in English with the words "pre-pubertal" OR "boys" OR "p(a)ediatric" OR "children" AND "epididymitis" OR "epididymo-orchitis". RESULTS The literature suggests that it is rare to find a bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…Previous studies have demonstrated that most pediatric males with epididymitis do not have pyuria on urinalysis or a positive urine culture and, therefore, do not require routine antibiotic treatment . As there are no clear predictors for males with a bacterial etiology of epididymitis the general recommendation is for a urine culture to be performed on males with epididymitis, while the utility of a screening urinalysis for pyuria is less clear. In our study cohort urinalysis was performed in 86% of males without testicular torsion and 0% in males with torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that most pediatric males with epididymitis do not have pyuria on urinalysis or a positive urine culture and, therefore, do not require routine antibiotic treatment . As there are no clear predictors for males with a bacterial etiology of epididymitis the general recommendation is for a urine culture to be performed on males with epididymitis, while the utility of a screening urinalysis for pyuria is less clear. In our study cohort urinalysis was performed in 86% of males without testicular torsion and 0% in males with torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the use of DUS may prolong the time in testicular ischemia and delay time to surgery for those with testicular torsion . In addition to DUS, laboratory testing with urinalysis and urine culture and for sexually transmitted infections (STIs) is used in the evaluation of testicular complaints to evaluate for other causes of the acute scrotum, including epididymitis …”
Section: Importancementioning
confidence: 99%
“…However, this is a controversial problem in prepubertal boys. The causes of epididymoorchitis in prepubertal boys are infectious agents (bacterial, viral, fungal), genitourinary tract abnormalities, postinfectious inflammatory reactions, vasculitides, certain medications or local trauma (3,5). In patients with epididymoorchitis, urine cultures correlate well with epididymal aspirates, so especially in children aspiration is not recommended, urine is sufficient for laboratory investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak bu prepubertal erkek çocuklarında tartışmalı bir sorundur. Prepubertal erkek çocuklarında epididimoorşit nedenleri enfeksiyöz etkenler (bakteriyel, viral, fungal), genitoüriner sistem anomalileri, postinfeksiyöz inflamatuvar reaksiyonlar, vaskülitler, bazı ilaçlar veya lokal travmalardır (3,5). Epididimoorşitli hastalarda, idrar incelemeleri ve kültürleri epididimal aspirat örneklerinin değerlendirlmesiyle iyi korelasyon gösterir.…”
Section: Olgu Sunumuunclassified